2021
DOI: 10.3390/ma14174907
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle-Coated Polyhydroxyalkanoate Based Electrospun Fibers for Wound Dressing Applications

Abstract: Wound dressings are high performance and high value products which can improve the regeneration of damaged skin. In these products, bioresorption and biocompatibility play a key role. The aim of this study is to provide progress in this area via nanofabrication and antimicrobial natural materials. Polyhydroxyalkanoates (PHAs) are a bio-based family of polymers that possess high biocompatibility and skin regenerative properties. In this study, a blend of poly(3-hydroxybutyrate) (P(3HB)) and poly(3-hydroxyoctano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…PHA containing repeat units with longer side chains, such as PHO and copolymers, usually have lower crystallinities and can even be fully amorphous [ 37 ]. Moreover, PHO has been stated as a promising material because it is biocompatible, non-toxic, thermoplastic, and/or elastomeric, which are appealing properties for consumer and specialized applications [ 17 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHA containing repeat units with longer side chains, such as PHO and copolymers, usually have lower crystallinities and can even be fully amorphous [ 37 ]. Moreover, PHO has been stated as a promising material because it is biocompatible, non-toxic, thermoplastic, and/or elastomeric, which are appealing properties for consumer and specialized applications [ 17 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that a wide variety of bacteria possess the ability to use biomass as a reducing agent, in particular species of the genera Lactobacillus and Bacillus , some strains of Escherichia coli, and Alcaligenes eutrophus , previously known as Cupriavidus necator [ 15 , 16 ]. Biologically synthesized silver nanoparticles (Bio-AgNPs) have been successfully incorporated into synthetic polymers commonly used in biomedicine, such as polycaprolactone (PCL) [ 8 ], and more recently into bio-based polymers from the family of polyhydroxyalkanoates (PHAs) [ 16 , 17 , 18 , 19 , 20 ], opening a new field of synthesis of antimicrobial wound dressings.…”
Section: Introductionmentioning
confidence: 99%
“…The surface charge and surface wettability and can be considerably enhanced by incorporation of antimicrobial agents such as metal/metal oxide NPs, carbon nanomaterials, AMPs or natural plant or herbal extracts. The functionalization of electrospun nanofibers with antimicrobial agents can be utilized to fight bacterial infections and resistance and is a promising strategy to combat bacterial infection and resistance [ 188 , 189 , 190 , 191 ]. The ethylcellulose/gum tragacanth (85:15) electrospun nanofibrous mats with incorporated honey (5–20 wt%) were evaluated as an effective wound covering biomaterials characterized with antibacterial properties, improved antioxidant activity, good mechanical properties and degradation ability features, and showed proper cell growth, attachment, and proliferation against NIH-3 T3 fibroblast cells [ 192 ].…”
Section: Applied Nanomaterialsmentioning
confidence: 99%
“…Wound dressings with adequate air permeability, water sorption, and good resistance against microbial organisms were also obtained by dip-coating of polyester/viscose samples in the presence of biogenic silver nano sol (AgNS) prepared using manuka honey [ 169 ]. In another study, poly(3-hydroxybutyrate) (P(3HB))/poly(3-hydroxyoctanoate-co-3-hydroxy decanoate) (P(3HO-co-3HD)) nanofibers were prepared via electrospinning, then an aqueous colloidal silver solution of 4000 ppm was used for dip-coating of nanofibrous scaffolds with dimensions of 30 mm × 60 mm at a rate of 170 mm/min to obtain antimicrobial wound dressings [ 170 ].…”
Section: Wound Dressingsmentioning
confidence: 99%